Integrating Product Platform Development with Supply Chain Configuration in a Global Environment - Ghosh, Soumen (Institutional Knowledge at Singapore Management University, 2004)
In this research, we have investigated the interaction between product platform development and supply chain configuration in a global environment. A comprehensive decision support model has been developed to simultaneously determine product strategy and supply chain configuration. By Products we refer to the bundle of module option alternatives offered to market segments, and product platform development is a means of looking for the opportunity of sharing module option alternatives among products. A scenario analysis has been performed to gain insights on how platform development is influenced by market conditions and current supply chain configuration. The analysis shows that different supply chain configurations favour different levels of platforming. It also shows that decentralised manufacturing and sourcing configuration does not necessarily support a higher degree of customisation.